Morphologic determinant of tight junctions revealed by claudin-3 structures - Shun Nakamura (Nature Portfolio, 2019)
The main components of tight junctions (TJ) are claudins that polymerize and form meshwork architectures called TJ strands. Here the authors present the 3.6 Å crystal structure of murine claudin-3 and show that residue P134 causes a bending of the third transmembrane helix which affects the morphology and adhesiveness of the TJ strands.